PEGOGIC CREATIVITY OF A MUSIC CULTURE TEACHER - Fozilov Qahramon Madaminovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article will talk about the pedagogical creativity of the teacher of music culture, the source of pedagogical creativity, the creative mood of the teacher and the educational and educational work of the music teacher.